Study of the rare decay J/ψ → μ+μ−μ+μ− - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
The rare electromagnetic J/ψ → μ+μ−μ+μ− decay is observed with a significance greatly exceeding the discovery threshold, using proton-proton collision data collected by the LHCb experiment during 2016-2018 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.4 fb−1. The rate of this decay is measured relative to that of the J/ψ → μ+μ− mode. Using the QED model for the four-muon decay in the efficiency estimation, its branching fraction is determined to beBJ/ψ→μ+μ−μ+μ−=1.13±0.10±0.05±0.01×10−6, where the uncertainties are statistical, systematic and due to the uncertainty on the branching fraction of the J/ψ → μ+μ− decay.
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov und weitere1088
Im Titel sind die Zeichen "+" und "-" hochgestellt
Gesehen am 09.07.2025